Oral Presentation No. 083 Coronary Aspiration Thrombectomy: bringing back the old kid on the block. (21st October 2022) - de Almeida, António Rocha; Neves, David; Figueiredo, Marta; Sousa, Miguel Carias; Cláudio, Francisco; Rocha, Rita; Trinca, Manuel
Abstract: Background: Traditionally, routine thrombus aspiration during primary percutaneous coronary intervention (PCI) was performed to prevent distal embolization and protect microvascular perfusion. However, recent trials showed no clinical benefits (except if high thrombotic burden). Despite not being routinely recommended, thrombus aspiration should still be considered in highly thrombotic circumstances. Material and methods: Prospective cohort of 50 patients admitted to primary PCI, with aspiration thrombectomy (AT), between 2019–2022, was analyzed. In evidence of high thrombotic burden, AT was performed, if technically possible. Success was evaluated angiographically and by TIMI flow improvement. Safety was assessed by neurologic evaluation, verified CT-scan, in 30 days follow-up. Results and conclusions: 50 patients were analyzed, with mean age of 59, 6 ± 1, 8 years, being 22% women ( n = 11). 88% ( n = 44) presented ST-segment elevation myocardial infarction Killip 1, 2% ( n = 1) Killip 3 and 10% ( n = 5) Killip 4. There was thrombus aspiration angiographic evidence in 76% ( n = 38) and TIMI flow increase in 82% ( n = 41) cases with median improvement of 2 [IR 1, 3]. In 20% ( n = 10) cases, stent wasn't implanted. There was significant statistical association between no stent PCI and angiographical thrombus reduction ( P < 0, 05, OR 3, 86). There were no deaths, major adverse cardiovascular events (MACE), or neurologic complications in any patient ( n = 0) within 30 days. Routine coronary AT shouldn't be performed. It is useful, however, in selected cases with evidence of angiographic thrombus aspiration and TIMI flow improvement. Successful AT was associated with no stent PCI. Regarding safety, there was no statistically significant increase of death of any cause, MACE, or stroke.